2018
DOI: 10.1093/jxb/ery226
|View full text |Cite
|
Sign up to set email alerts
|

Drought tolerance during reproductive development is important for increasing wheat yield potential under climate change in Europe

Abstract: Drought stress during reproductive development could drastically reduce grain number and wheat yield, but quantitative evaluation of such effect is unknown under climate change. The objectives of this study were to a) evaluate potential yield benefits of drought tolerance during reproductive development for wheat ideotypes under climate change in Europe, and b) identify potential cultivar parameters for improvement. We used the Sirius wheat model to optimise drought tolerant (DT) and drought sensitive (DS) whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(112 citation statements)
references
References 80 publications
6
93
0
2
Order By: Relevance
“…Therefore, supplemental irrigation during this period is pivotal to mitigate the effects of water deficit stress. The decrease in NGE would be one of the most significant effects of water deficit stress (Honsdorf et al 2017, Senapati et al 2019. Our results are supported by a previous study by Saedi et al (2012), which showed that water deficit during the grain filling stages significantly reduced WTG and thus grain yield, especially in more sensitive varieties.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, supplemental irrigation during this period is pivotal to mitigate the effects of water deficit stress. The decrease in NGE would be one of the most significant effects of water deficit stress (Honsdorf et al 2017, Senapati et al 2019. Our results are supported by a previous study by Saedi et al (2012), which showed that water deficit during the grain filling stages significantly reduced WTG and thus grain yield, especially in more sensitive varieties.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, our results regarding the agro-morphological traits of soybean confirm previous studies [22] in that most of the traits were affected by water deficit. However, it is reported that genotypes and duration of stress also determined the severity of the effects of a water deficit [23,24]. Growth traits such as plant height, stem diameter, number of nodes per plant and number of branches per plant did not show significant results.…”
Section: Effect Of Split-root Water Imbalance Treatments On Agro-morpmentioning
confidence: 91%
“…The interactive effects of the AMF R. irregularis and the PGPB P. putida synergistically improved the growth and defence of the wheat host plants against pathogens [156]. With the global warming, drought has been one of the major limiting conditions for crop production [157]. Studies have shown that AMFs enhanced rice and wheat in resisting drought by improving the plant physiological index [158,159].…”
Section: Applications Of Individual Microbes For Improvement Of Crop mentioning
confidence: 99%